Bilinexin, a Snake C-type Lectin from Agkistrodon bilineatus Venom Agglutinates Platelets via GPIb and α2β1 - Du, Xiao-Yan; Navdaev, Alexey; Clemetson, Jeannine M.; Magnenat, Edith; Wells, Timothy N. C.; Clemetson, Kenneth J. (Thrombosis and Haemostasis, 2001)
A new snake protein, named bilinexin, has been purified from Agkistrodon bilineatus venom by ion-exchange chromatography and gel filtration chromatography. Under non-reducing conditions it has a mass of 110 kDa protein on SDS-PAGE. On reduction, it can be separated into five subunits with masses in the range 13-25 kDa. The N-terminal sequences of these subunits are very similar to those of convulxin or the alboaggregins, identifying bilinexin as a new member of the snake C-type lectin family, unusual in having multiple subunits. Bilinexin agglutinates fixed platelets, washed platelets and platelet rich plasma (PRP) without obvious activation (shape change) as confirmed by light microscope examination. Both inhibitory and binding studies indicate that antibodies against α2β1 inhibit not only platelet agglutination induced by bilinexin, but also bilinexin binding to platelets. VM16d, a monoclonal anti-GPIbα antibody, completely inhibits platelet agglutination induced by bilinexin, and polyclonal antibodies against GPIbα prevent its binding to platelets. However, neither convulxin, polyclonal anti-GPVI antibodies, nor GPIIb/IIIa inhibitors affect its binding to and agglutination of platelets. Bilinexin neither activates GPIIb/IIIa integrin on platelets nor induces tyrosine phosphorylation of platelet proteins, nor increases intracellular Ca2+ in platelets. Like alboaggregin B, bilinexin agglutinates platelets, which makes it a good tool to investigate the differences in mechanism between snake C-type lectins causing platelet agglutination and those that induce full activation.
Keywords: Bilinexin; platelet agglutination; GPIb; α2β1